2008
DOI: 10.1074/jbc.m709262200
|View full text |Cite
|
Sign up to set email alerts
|

Cleaved Serpin Refolds into the Relaxed State via a Stressed Conformer

Abstract: Serine proteinase inhibitors (serpins) are believed to fold in vivo into a metastable "stressed" state with cleavage of their P1-P1 bond resulting in reactive center loop insertion and a thermostable "relaxed" state. To understand this unique folding mechanism, we investigated the refolding processes of the P1-P1-cleaved forms of wild type ovalbumin (cl-OVA) and the R339T mutant (cl-R339T). In the native conditions, cl-OVA is trapped as the stressed conformer, whereas cl-R339T attains the relaxed structure. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Constraining the gate itself may also be important, as conformational changes in this region have been implicated in pathological serpin polymerization (26), which can occur in the ER during serpin maturation. For the serpins α 1 -antitrypsin and ovalbumin, both of which lack C-terminal disulfide bonds, purified protein-folding studies have demonstrated the importance of the C-terminal region for proper folding and function (27)(28)(29)(30). These results highlight the importance of constraining conformationally labile regions early in serpin folding to efficiently reach the functionally required metastable structure.…”
Section: Atiiimentioning
confidence: 88%
“…Constraining the gate itself may also be important, as conformational changes in this region have been implicated in pathological serpin polymerization (26), which can occur in the ER during serpin maturation. For the serpins α 1 -antitrypsin and ovalbumin, both of which lack C-terminal disulfide bonds, purified protein-folding studies have demonstrated the importance of the C-terminal region for proper folding and function (27)(28)(29)(30). These results highlight the importance of constraining conformationally labile regions early in serpin folding to efficiently reach the functionally required metastable structure.…”
Section: Atiiimentioning
confidence: 88%
“…Electrostatic repulsion between K342 and K290 may promote polymerization by delaying the already slow insertion of strand 5A, which would be consistent with a loop sheet or RCL-strand 5A domain swap model for polymerization. Another possibility-suggested both by the study of Onda et al (12) and by that of Krishnan and Geirasch (6)-is that much of the molecule can adopt a native-like topology even before the formation of stable hydrogen bonds. In this case, positioning of β-strand 5A across the front of sheet B (but not its stable incorporation into sheet A) may be required for the subsequent folding of the C-terminal residues to proceed (see note).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of proper formation of the B-C barrel in serpin folding is also highlighted by a study of an ovalbumin mutant that spontaneously adopts the stable loop inserted structure (12). When a fragment consisting of the first 352 residues was diluted from 8 M urea, it adopted a structure with the properties of the metastable state, including an exposed RCL.…”
Section: Discussionmentioning
confidence: 99%
“…Limited Proteolysis-The core region involved in the fibril was mapped by identifying the local region that is not susceptible to proteolytic cleavage as reported previously (22,40,43). A 2 mg/ml solution of OVA was heat-treated at 80°C for 1 h and then digested with trypsin for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Proteolytic cleavage generally occurs at flexible regions of a polypeptide chain, and the structured regions of the amyloid fibril correspond to the most highly protease-resistant region. In this study, the protease-resistant region of the OVA fibril was assessed using trypsin, which is a particularly appropriate protease for these studies because the native conformation of OVA is highly resistant to trypsin but not in its non-native conformation (22,40,43). The heat-induced aggregates of intact OVA and SH-OVA were treated with trypsin, and the cleavage products were separated by 15% SDS-PAGE.…”
Section: Mvlvmentioning
confidence: 99%